MET Exon 14 Skipping Mutations in Lung Cancer: Clinical–Pathological Characteristics and Immune Microenvironment. - Xue, Qianqian; Wang, Yue; Zheng, Qiang; Huang, Ziling; Lin, Yicong; Jin, Yan; Li, Yuan (Current Oncology, 2025)
Simple Summary: Lung cancer is a leading cause of cancer-related deaths, but new treatments targeting specific gene changes have improved outcomes for many patients. One such change, called MET exon 14 skipping, occurs in a small group of patients and is linked to more aggressive tumors. While targeted therapies have shown promise, the benefit of immunotherapy in these patients remains unclear. In this study, we used a special technique to examine the immune environment of tumors with this mutation. We looked closely at immune cells and how they interact with cancer cells. Our goal was to better understand why some patients respond to treatment while others do not. Although the number of cases in our study was limited, our findings offer early clues that may help guide future research, improve treatment strategies, and eventually lead to more personalized care for patients with this type of lung cancer. MET exon 14 skipping mutations have emerged as significant driver alterations in non-small-cell lung cancer (NSCLC), contributing to tumor progression. This study examines the immune microenvironment in NSCLC patients with these mutations and its prognostic implications. We performed multiplex immunofluorescence (mIF) staining on formalin-fixed paraffin-embedded (FFPE) tissue samples from nine NSCLC patients, including four recurrent/metastatic and five non-recurrent/non-metastatic patients. Two panels assessed immune cell markers (CD8, CD4, CD20, CD68, and FoxP3) and immune checkpoints (PD-L1, LAG3, and TIM3). Immune cell infiltration and checkpoint expression were analyzed using HALOTM software (version 3.6.4134.464). Nearest neighbor analysis was conducted to assess the proximity of immune cells to tumor cells. Univariate Cox regression analysis assessed factors associated with disease-free survival (DFS). CD8+TIM3+ and CD8+LAG3+ cells were predominantly located in the tumor parenchyma of recurrent/metastatic patients but localized to the stroma in non-recurrent/non-metastatic patients. Non-recurrent/non-metastatic patients exhibited a higher density of tertiary lymphoid structures and closer proximity of CD20+ B cells, CD8+TIM3+, and CD8+LAG3+ cells to tumor cells compared to recurrent/metastatic patients, though the differences were not statistically significant. Cox regression analysis suggested a potential association between higher densities of CD8+TIM3+ cells and improved DFS (HR = 0.89), though these findings did not reach statistical significance. Our findings suggest that differences in immune microenvironmental factors, particularly those related to immune checkpoint expression (TIM3 and LAG3), may influence clinical outcomes in NSCLC patients with MET exon 14 skipping mutations. Further studies are needed to validate these observations and explore potential therapeutic implications.